Optimizing Bowel Preparation in Small Bowel Capsule Endoscopy: It's All About Timing - Jearth, Vaneet; Dogra, Kshitiz (Journal of Digestive Endoscopy, 2025)
Small bowel capsule endoscopy (SBCE) allows for radiation-free and noninvasive visualization of small bowel (SB) mucosa with high-quality images and is critical in the management of a variety of conditions, including suspected SB bleeding, suspected or definitive SB Crohn's disease, SB tumors including intestinal polyposis syndromes, and, to a lesser extent, celiac disease. The optimal preparation protocol remains a subject of considerable debate, with no universally accepted bowel cleansing regimen identified to achieve the desired performance measure. In this news and views, we discuss a recently published multicenter, prospective, single-blinded (for investigators) randomized controlled trial in patients for whom SBCE was performed for suspected SB bleeding to ascertain the optimal timing and preparation for SBCE.
Keywords: small bowel capsule endoscopy; suspected small bowel bleed; diagnostic yield